An Intraventricular Schwannoma with Associated Hydrocephalus and Ventricular Entrapment: A Case Report - Sheilah M. Curran-Melendez; Melanie Fukui; William Bivin; David Oliver-Smith (Journal of Neurological Surgery Reports, 2015)
Abstract Intraventricular schwannomas are rare primary brain tumors, with fewer than 25 cases reported in the literature. Here, we present the case of a 20-year-old male patient with a 2 year history of blurry vision and dysesthesia involving his right occiput and upper neck. Imaging demonstrated a homogeneously enhancing mass located within the atrium of the right lateral ventricle with associated right lateral ventricular entrapment. Pathology confirmed the tumor to be an intraventricular schwannoma. Imaging findings, presentation, complications, and treatment options for intraventricular schwannomas are described.